Penerapan Ajaran Kausalitas Pada Kecelakaan Lalu Lintas Yang mengakibatkan Kematian - Eugara, Lukas Putra; Hehanussa, Deassy Jacomina Anthoneta; Latupeirissa, Julianus Edwin (Faculty of Law, Universitas Pattimura, 2024)
Introduction: The teaching of causality in criminal law or better known as a causal relationship is very interesting. There are various theories of causality known in criminal law. These theories were born to answer one important question in criminal law, namely what is the cause of an effect. Often in the event of a traffic accident the focus in solving is only on the facts of the incident but the presence of causality becomes a filter to see which is the cause of the effect.Purposes of the Research: This study aims to analyze and discuss the application of causality to traffic accidents that result in death.Methods of the Research: This research is a normative legal research. In this study, the approach used is the legal approach. Sources of data obtained are primary legal materials and secondary legal materials. The technique of collecting legal materials is by means of library research by collecting materials through invitations, reference books, mass media, such as newspapers. The overall data in this study were analyzed qualitatively.Results of the Research : The results of this study indicate that the application of the teaching of causality to traffic accidents resulting in death has its own problems where law enforcers, both the police, prosecutors and judges, always use the theory/doctrine of causality because the causality teaching has not been clearly defined, so the application that is present only one or two doctrines from the teachings of causality, be it the theory of conditio sine quo non, generalizing, individualizing, to relevance. Therefore it is very important to provide technical guidelines for judges and prosecutors in interpreting, exploring, analyzing, and applying the teachings of causality so that the process of finding causes that cause prohibited effects produces a truth.